PERBEDAAN HASIL BELAJAR KIMIA PESERTA DIDIK DENGAN METODE PROBLEM SOLVING DAN METODE INVESTIGASI - Ratna Sari Dewi (Faktor Jurnal Ilmiah Kependidikan, 2014)
Abstract This study aims to obtain empirical evidence about differences in learning outcomes of students who are taught to approach and Problem Posing Approach to the investigation material the chemical bondin Class X SMA Harapan 1 Medan shavings Academic Year 2013/2014 . The method used was experimental . The population was class X SMA Harapan 1 Medan shavings Academic Year 2013/2014 which consists of two classes , the X - 1 as the experimental group and class X - 2 as a control group class (applying investigative approach.). To obtain the necessary data in this study used a test in the form of a description as much as 6 questions . The data were analyzed with statistical analysis .From the analysis of data obtained by the average and standard deviation of students who are taught to approach and Problem Posing. Mean and standard deviation of students who are taught to approach  and  Investigation   and   . Keywords : Problem Posing Approach , investigative approach , the chemical bond